Socrative as Online Formative Assessment to Foster Reading Comprehension - Putri, Dzinnuraini Maulina; Prastikawati, Entika Fani; Wiyaka, Wiyaka (STAIN Sultan Abdurrahman Kepulauan Riau, 2023)
The use of technology in education plays a vital role in language assessment. The change in educational adjustment during the COVID-19 period requires teachers to use technology in learning. The teachers need to know the effect of students' achievement and students' perceptions in using online assessment tools. This research aimed to investigate the students' improvement of reading comprehension and students' perception of Socrative as an online formative assessment. This study applied a quasi-experimental design and a closed questionnaire to collect data. Two classes consisted of 32 students (16 students in the control class; 16 students in the experimental class) who participated in this study in SMA Negeri 1 Cepiring, Central Java, Indonesia. The collected data were then analyzed quantitatively using SPSS 23. The result showed that Socrative effectively improves the students' reading comprehension. Socrative is effective as an alternative online formative assessment in improving the students' reading comprehension compared to the paper-based formative assessment. Another result revealed positive perceptions of Socrative as an online formative assessment for improving students' reading comprehension. They claimed that Socrative brings a new atmosphere and innovative formative assessment process that helps improve students' reading comprehension. For facts, Socrative can be considered as an innovative and effective online formative assessment that is worthed to apply by the english teachers or educators.